Nitric oxide as a mediator of inflammation?—You had better believe it - Mark J. S. Miller; Matthew B. Grisham (Mediators of Inflammation)
Nitric oxide has enigmatic qualities in inflammation. In order to appreciate the precise contributions of nitric oxide to a pathophysiological process, one must account for enzyme source, coproduction of oxidants and antioxidant defences, time, rate of nitric oxide production, cellular source, peroxynitrite formation and effects on DNA (mutagenesis/apoptosis). We contend that there is ample evidence to consider nitric oxide as a molecular aggressor in inflammation, particularly chronic inflammation. Therapeutic benefit can be achieved by inhibition of inducible nitric oxide synthase and not the donation of additional nitric oxide. Furthermore, there is growing appreciation that nitric oxide and products derived thereof, are critical components linking the increased incidence of cancer in states of chronic inflammation.